Cyber security testing and intrusion detection for synchrophasor systems. (2016) - Morris, Thomas; Pan, Shengyi; Adhikari, Uttam; Younan, Nicolas; King, Roger; Madani, Vahid
Synchrophasor systems are an emerging technology. Prior to installation of a synchrophasor system a set of cyber security requirements must be developed, new devices must undergo vulnerability testing, and proper security controls must be designed to protect the synchrophasor system from unauthorised access. This paper describes the process taken to develop a set of cyber security requirements for an American Recovery and Reinvestment Act (ARRA) funded synchrophasor project. The paper further describes vulnerability analysis and testing performed on synchrophasor system components. Finally, the paper describes intrusion detection rules written as a response to vulnerabilities discovered in the vulnerability analysis and testing process.